Conductive composition, die attach material, pressure sintered die attach material and electronic parts
A conductive composition with silver particles and controlled thermosetting resin achieves high die shear strength in semiconductor bonding, addressing inefficiencies in low-temperature and short-time heat treatment processes.
Patent Information
- Application Number
- JP2022541128
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-04
- Filing Date
- 2021-06-02
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-06-02
AI Technical Summary
Conventional conductive compositions face challenges in achieving sufficient die shear strength through low-temperature or short-time heat treatment, making the bonding process inefficient.
A conductive composition comprising silver particles with specific size ranges, a solvent, and a thermosetting resin with controlled saponifiable chlorine concentration, allowing for excellent die shear strength through low-temperature or short-time heat treatment, regardless of pressure application.
The composition enables effective bonding with high die shear strength, suitable for semiconductor devices, even with low-temperature or short-time heat treatment, enhancing productivity and efficiency.
Smart Images

Figure 0007619656000001 
Figure 0007619656000002 
Figure 0007619656000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive composition, a die attachment material, a pressure sintered die attachment material, and an electronic component. More specifically, the present invention relates to a conductive composition capable of sintering silver particles together even at a low temperature or in a short time, thereby realizing excellent die shear strength, and to a die attachment material, a pressure sintered die attachment material, and an electronic component that include such a conductive composition. [Background technology]
[0002] In recent years, from the viewpoint of productivity, there has been a demand for conductive compositions that have sufficient conductivity by sintering silver particles together even with low-temperature or short-time heat treatment, regardless of whether pressure is applied or not, for materials used in bonding various components of semiconductor devices and electric / electronic parts, such as die attach materials.
[0003] As a technique for bonding components in a semiconductor device, for example, a method has been proposed in which a die attach material is placed between a base and a semiconductor element, and the semiconductor element and the base are heated to bond the semiconductor element and the base (see, for example, Patent Document 1).
[0004] For example, Patent Document 1 discloses a method for bonding a semiconductor element and a base through the following three steps. The first step is a step of arranging the silver or silver oxide applied to the surface of the semiconductor element so that the silver or silver oxide applied to the surface of the base is in contact with the silver or silver oxide applied to the surface of the base. The second step is a step of applying pressure or ultrasonic vibration to the semiconductor element or the base to temporarily bond the semiconductor element and the base. And the third step is a step of applying a temperature of 150°C to 900°C to the semiconductor element and the base to permanently bond the semiconductor element and the base. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2010 / 084742 Summary of the Invention [Problem to be solved by the invention]
[0006] However, conventional conductive compositions such as die attach materials have a problem in that it is difficult to achieve sufficient die shear strength by low-temperature or short-time heat treatment. For example, in Example 14 of Patent Document 1, a substrate to which a semiconductor light-emitting element is temporarily bonded is heated in a nitrogen gas flow at about 320°C for about 30 minutes to perform the main bonding. With such a conductive composition, bonding takes time, and there is a problem in that it is not possible to sufficiently achieve both low-temperature or short-time sintering and die shear strength.
[0007] The present invention has been made in consideration of the problems associated with the conventional techniques. The present invention provides a conductive composition that can sinter silver particles together even with low-temperature or short-time heat treatment, regardless of whether pressure is applied or not, to achieve excellent die shear strength. The present invention also provides a die attachment material, a pressure-sintered die attachment material, and an electronic component that include the above-mentioned conductive composition and achieve excellent die shear strength. [Means for solving the problem]
[0008] According to the present invention, there are provided a conductive composition, a die attachment material, a pressure sintered die attachment material, and an electronic component, which are shown below.
[0009] [1] A composition comprising: (A) silver particles having an average particle size of 0.05 to 5 μm; (B) a solvent; and (C) a thermosetting resin; (C) the easily saponifiable chlorine concentration of the thermosetting resin is 3,000 to 12,000 ppm; A conductive composition comprising 0.1 to 1.5 parts by mass of a thermosetting resin (C) relative to 100 parts by mass of silver particles (A).
[0010] [2] The conductive composition according to [1] above, wherein the thermosetting resin (C) comprises an epoxy resin.
[0011] [3] The conductive composition according to [1] or [2] above, wherein the (A) silver particles include fine silver particles having an average particle size of 0.05 to 0.5 μm.
[0012] [4] A die attach material comprising the conductive composition according to any one of [1] to [3] above.
[0013] [5] A pressure sintered die attach material comprising the conductive composition according to any one of [1] to [3] above.
[0014] [6] An electronic device comprising a sintered body of the conductive composition according to any one of [1] to [3] above. Effect of the Invention
[0015] The conductive composition of the present invention has the effect of sintering silver particles together even with low-temperature or short-time heat treatment, regardless of whether pressure is applied or not, thereby realizing excellent die shear strength. Furthermore, the die attach material, pressure sintered die attach material, and electronic component of the present invention contain the conductive composition of the present invention described above, and have the effect of having excellent die shear strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following describes the embodiments of the present invention, but the present invention is not limited to the following embodiments. Therefore, it should be understood that the scope of the present invention includes any modifications and improvements to the following embodiments based on the ordinary knowledge of a person skilled in the art without departing from the spirit of the present invention.
[0017] [Conductive composition] An embodiment of the conductive composition of the present invention is a conductive composition containing (A) silver particles having an average particle size of 0.05 to 5 μm, (B) a solvent, and (C) a thermosetting resin. The conductive composition of this embodiment is used for bonding members of semiconductor devices such as die attach materials and electric / electronic components. Hereinafter, "(A) silver particles having an average particle size of 0.05 to 5 μm" may be simply referred to as "(A) silver particles."
[0018] The conductive composition of this embodiment has an easily saponifiable chlorine concentration of the (C) thermosetting resin of 3,000 to 12,000 ppm, and contains 0.1 to 1.5 parts by mass of the (C) thermosetting resin per 100 parts by mass of the (A) silver particles. The conductive composition thus configured can sinter the silver particles together even with low-temperature or short-time heat treatment, regardless of whether pressure is applied or not, thereby achieving excellent die shear strength. Each component constituting the conductive composition of this embodiment will be described in more detail below.
[0019] [(A) Silver particles] (A) silver particles are particles containing silver (Ag) or a silver alloy. The shape of the (A) silver particles is not particularly limited, and may be any shape, such as spherical, flake-like, scale-like, or needle-like. As the (A) silver particles, silver particles containing a mixture of silver particles of different shapes may be used. Note that a large number of silver particles (Ag particles) may be referred to as silver powder (Ag powder). The same applies to other particles.
[0020] The (A) silver particles preferably have an average particle size of 0.05 to 5 μm, and from the viewpoint of sinterability, silver particles of 1.5 μm or less are more preferable. In this specification, the silver particles and silver fine particles may be used in the form of primary particles, secondary particles, or a mixture of primary particles and secondary particles. When used as primary particles, the average particle size can be measured by the average particle size (number average) when 200 primary particles are observed with a scanning electron microscope (SEM). When used as secondary particles, the average particle size can be measured by the average particle size (number average) when 200 secondary particles are observed with a scanning electron microscope (SEM). When primary particles and secondary particles are mixed, the average particle size can be measured by the average particle size (number average) when a total of 200 primary particles and secondary particles are observed with a scanning electron microscope (SEM). The magnification of the SEM when observing silver particles and silver fine particles can be appropriately selected as appropriate. Usually, a magnification of 3000 to 50000 times is used. The primary particles and secondary particles are defined according to JIS H7008 (ultrafine metal particles).
[0021] The method for producing the (A) silver particles is not particularly limited, and for example, the (A) silver particles can be produced by a reduction method, a pulverization method, an electrolysis method, an atomization method, a heat treatment method, or a combination thereof.
[0022] The (A) silver particles may contain (a) fine silver particles having an average particle size of 1 μm or less. By containing (a) fine silver particles, the die shear strength can be further increased.
[0023] The (a) silver fine particles have an average particle size of preferably 0.05 to 0.5 μm, more preferably 0.05 to 0.4 μm, and even more preferably 0.05 to 0.2 μm. The (a) silver fine particles are usually approximately spherical. When the (a) silver fine particles have an average particle size within the above range, aggregation of the (a) silver fine particles and the (A) silver particles containing the (a) silver fine particles is suppressed, and storage stability is easily obtained.
[0024] The (a) silver fine particles preferably have a crystallite diameter of 20 to 70 nm, more preferably 20 to 50 nm. When the crystallite diameter is within this range, volume shrinkage during firing is suppressed, and the denseness and surface smoothness of the bonded joint formed after firing are ensured.
[0025] The (a) silver fine particles have a ratio of the average particle size to the crystallite size of the silver fine particles (average particle size / crystallite size) of preferably 1.5 to 5, more preferably 1.5 to 4, and even more preferably 1.5 to 3. When the ratio is within this range, an adhesive joint exhibiting sufficient conductivity can be formed, for example, at a baking temperature of 200° C. or less.
[0026] As the (a) silver fine particles, silver fine particles obtained by reacting a silver salt of a carboxylic acid with a primary amine and then precipitating by a reduction reaction, or silver fine particles coated or treated with an organic substance can be used. Examples of the former include the silver fine particles disclosed in JP 2006-183072 A and JP 2011-153362 A, and examples of the latter include the silver fine particles disclosed in JP 2009-289745 A and JP 2010-65277 A. In addition, as the (a) silver fine particles, silver fine particles disclosed in WO 2017 / 169534 A and the like can also be used. (a) Silver particles are on the nano-order, have a large total surface area per unit weight, and have high surface energy. In addition to having good sinterability to begin with, during sintering, organic matter on the surface volatilizes, pyrolyzes, or dissolves into the solvent, exposing the silver surface. This causes the (a) silver particles to come into direct contact with each other, making it easy for sintering to proceed.
[0027] Specifically, (a) fine silver particles can be prepared by mixing a silver salt of a carboxylic acid with an aliphatic primary amine, then adding a reducing agent and causing precipitation at a reaction temperature of 20 to 80°C.
[0028] The silver salt of carboxylic acid is not particularly limited. The silver salt of carboxylic acid may be either an aliphatic or aromatic carboxylic acid. In addition, it may be a silver salt of a monocarboxylic acid or a silver salt of a polyvalent carboxylic acid such as a dicarboxylic acid. The silver salt of aliphatic carboxylic acid may be a silver salt of a chain aliphatic carboxylic acid or a silver salt of a cyclic aliphatic carboxylic acid. A silver salt of an aliphatic monocarboxylic acid is preferable, more preferably a silver salt of a chain aliphatic monocarboxylic acid, and even more preferably silver acetate, silver propionate or silver butyrate, and particularly silver acetate. These can be used alone or in combination of two or more kinds.
[0029] The aliphatic primary amine is not particularly limited, and may be a chain aliphatic primary amine or a cyclic aliphatic primary amine. It may also be a monoamine compound or a polyamine compound such as a diamine compound. The aliphatic primary amine includes those in which the aliphatic hydrocarbon group is substituted with an alkoxy group such as a hydroxyl group, a methoxy group, an ethoxy group, or a propyl group, and more preferably, 3-methoxypropylamine, 3-aminopropanol, and 1,2-diaminocyclohexane. These may be used alone or in combination of two or more.
[0030] The amount of the aliphatic primary amine used is determined by the requirements and the equipment in the process such as post-treatment of the (a) silver fine particles to be prepared, but from the viewpoint of obtaining silver fine particles with a controlled particle size, it is preferable that the amount of the aliphatic primary amine used is 1.0 to 3.0 equivalents per equivalent of the silver salt of the carboxylic acid, more preferably 1.0 to 1.5 equivalents, and particularly preferably 1.0 to 1.1 equivalents, in consideration of the influence of the excess aliphatic primary amine on the environment, etc. For example, since the excess aliphatic primary amine may be vaporized by heating, it is desirable to adopt the above-mentioned preferred range of the amount used.
[0031] The mixing of the silver salt of carboxylic acid and the primary aliphatic amine can be carried out in the absence or presence of an organic solvent, and from the viewpoint of ease of mixing, it is preferable to carry out the mixing in the presence of an organic solvent. Examples of the organic solvent include alcohols such as ethanol, propanol, butanol, ethers such as propylene glycol dibutyl ether, and aromatic hydrocarbons such as toluene. These can be used alone or in combination of two or more. The amount of the organic solvent used can be any amount from the viewpoint of convenience of mixing and productivity of (a) silver fine particles in the subsequent process.
[0032] The silver salt of the carboxylate and the primary aliphatic amine can be mixed by, for example, adding the silver salt of the carboxylate while stirring the primary aliphatic amine or a mixture of the primary aliphatic amine and an organic solvent. After the addition is completed, stirring can be continued as appropriate. During this time, the temperature is preferably maintained at 20 to 80°C, more preferably 20 to 60°C.
[0033] Thereafter, a reducing agent is added to precipitate (a) fine silver particles. As the reducing agent, from the viewpoint of reaction control, formic acid, formaldehyde, ascorbic acid, or hydrazine is preferable, and formic acid is more preferable. These can be used alone or in combination of two or more kinds.
[0034] The amount of the reducing agent used is usually equal to or more than the redox equivalent of the silver salt of the carboxylic acid, and the redox equivalent is preferably 0.5 to 5 times, and more preferably 1 to 3 times. When the silver salt of the carboxylic acid is a silver salt of a monocarboxylic acid and formic acid is used as the reducing agent, the amount of formic acid used in molar terms is preferably 0.5 to 1.5 mol, more preferably 0.5 to 1.0 mol, and even more preferably 0.5 to 0.75 mol, per mol of the silver salt of the carboxylic acid.
[0035] In the addition of the reducing agent and the subsequent reaction, the temperature is preferably maintained at 20 to 80°C. The temperature in the addition of the reducing agent and the subsequent reaction is more preferably 20 to 70°C, and even more preferably 20 to 60°C. When the temperature is in this range, the particle growth of (a) the silver fine particles is sufficient, the productivity is high, and secondary aggregation is suppressed. The time required for the addition of the reducing agent and the subsequent reaction depends on the scale of the reaction apparatus, but is usually 10 minutes to 10 hours. In the addition of the reducing agent and the subsequent reaction, an organic solvent such as alcohols such as ethanol, propanol, butanol, ethers such as propylene glycol dibutyl ether, and aromatic hydrocarbons such as toluene can be additionally added as necessary.
[0036] In the addition of the reducing agent and the subsequent reaction, the amount (mol) of the silver salt of the carboxylic acid relative to the total volume (L) of the solution in which the silver salt of the carboxylic acid and the aliphatic primary amine are mixed, the reducing agent, and any organic solvent is preferably in the range of 1.0 to 6.0 mol / L, more preferably 2.0 to 5.0 mol / L, and even more preferably 2.0 to 4.0 mol / L. When the concentration is in this range, the reaction solution can be sufficiently stirred and the reaction heat can be removed, so that the average particle size of the precipitated (a) silver fine particles becomes appropriate, and thus there is no problem with operations such as precipitation decantation and solvent replacement in the subsequent steps.
[0037] When a reaction is carried out in a semi-batch system in which a solution of a silver salt of a carboxylic acid and an aliphatic primary amine are mixed in a reaction vessel and a reducing agent is continuously fed, the amount of precipitation of (a) silver fine particles per hour required from the start of addition of the reducing agent to the end of the reaction can be in the range of 0.3 to 1.0 mol / h / L per 1 L of the total volume of the solution of a silver salt of a carboxylic acid and an aliphatic primary amine, the reducing agent, and the optional organic solvent, and the productivity is very high. When the reaction is carried out in a continuous reaction system (continuous complete mixing tank or flow system), even higher productivity can be obtained, which is a great advantage for industrial implementation.
[0038] The (a) fine silver particles thus obtained have a narrow particle size distribution, and the geometric standard deviation can be made 2.0 or less. In this specification, the geometric standard deviation refers to the ratio (D84.3 value / D50 value) of the 84.3% particle size (D84.3 value) to the 50% particle size (D50 value) based on number, as determined by laser diffraction / scattering particle size distribution measurement.
[0039] The (a) silver fine particles precipitated by the reaction can be allowed to settle and the supernatant removed by decantation or the like, or a solvent such as an alcohol such as methanol, ethanol, or terpineol can be added to separate the silver fine particles. The layer containing the silver fine particles can be used as it is, including the solvent.
[0040] Alternatively, the (a) fine silver particles can be obtained by coating fine silver particles produced by a reduction method, a pulverization method, an electrolysis method, an atomization method, a heat treatment method, or a combination thereof, with an organic substance. From the viewpoint of low-temperature sintering, it is preferable to coat fine silver particles (a) produced by a reduction method with an organic substance.
[0041] The organic substances include high- and medium-chain fatty acids and their derivatives. Examples of the derivatives include high- and medium-chain fatty acid metal salts, high- and medium-chain fatty acid amides, high- and medium-chain fatty acid esters, and high- and medium-chain alkylamines. Among them, high- and medium-chain fatty acids are preferred.
[0042] Examples of higher fatty acids are fatty acids having 15 or more carbon atoms, and include linear saturated fatty acids such as pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), 12-hydroxyoctadecanoic acid (12-hydroxystearic acid), eicosanoic acid (arachidic acid), docosanoic acid (behenic acid), tetracosanoic acid (lignoceric acid), hexacosanoic acid (cerotic acid), and octacosanoic acid (montanic acid); branched saturated fatty acids such as 2-pentylnonanoic acid, 2-hexyldecanoic acid, 2-heptyldodecanoic acid, and isostearic acid; and unsaturated fatty acids such as palmitoleic acid, oleic acid, isooleic acid, elaidic acid, linoleic acid, linolenic acid, ricinoleic acid, gadoleic acid, erucic acid, and selacholeic acid.
[0043] The medium fatty acid is a fatty acid having 6 to 14 carbon atoms, and examples thereof include straight-chain saturated fatty acids such as hexanoic acid (caproic acid), heptanoic acid, octanoic acid (caprylic acid), nonanoic acid (pelargonic acid), decanoic acid (capric acid), undecanoic acid, dodecanoic acid (lauric acid), tridecanoic acid, and tetradecanoic acid (myristic acid); branched-chain saturated fatty acids such as isohexanoic acid, isoheptanoic acid, 2-ethylhexanoic acid, isooctanoic acid, isononanoic acid, 2-propylheptanoic acid, isodecanoic acid, isoundecanoic acid, 2-butyloctanoic acid, isododecanoic acid, and isotridecanoic acid; and unsaturated fatty acids such as 10-undecenoic acid.
[0044] (a) silver fine particles coated with higher fatty acids and their derivatives may be substituted with lower fatty acids. From the viewpoint of the sinterability and dispersion stability of (a) silver fine particles, silver fine particles coated with fatty acids having 12 to 18 carbon atoms are preferred. (a) silver fine particles may be used alone or in combination of two or more kinds.
[0045] The (a) silver fine particles are preferably sintered when the (a) silver fine particles in the conductive composition are held at a temperature of 180 to 250°C for 20 minutes to 2 hours. The (a) silver fine particles in the conductive composition are more preferably sintered when held at a temperature of 190 to 220°C for 20 minutes to 2 hours. The (a) silver fine particles in the conductive composition are even more preferably sintered when held at a temperature of 195 to 210°C for 20 minutes to 2 hours. If the (a) silver fine particles in the conductive composition can be sintered under the above conditions, the (a) silver fine particles contained in the conductive composition can form a joint that exhibits sufficient conductivity at a firing temperature of, for example, 200°C or less. Whether the (a) silver fine particles in the conductive composition are sintered by themselves when held at a temperature of 180 to 250°C for 20 minutes to 2 hours can be confirmed, for example, by a field emission scanning electron microscope (JSM7500F (product name)) manufactured by JEOL Ltd.
[0046] The content of the (A) silver particles in the conductive composition is not particularly limited, but from the viewpoint of ensuring sufficient thermal conductivity, it is preferably 75 to 93 mass%, more preferably 80 to 93 mass%, still more preferably 85 to 93 mass%, and particularly preferably 90 to 93 mass%, calculated as silver, relative to the entire conductive resin composition (100 mass%). The mass of the (A) silver particles in the conductive resin composition is defined as the remaining amount when the conductive resin composition is heated at 800°C for 5 minutes, which is taken as 100 mass%.
[0047] The conductive composition of this embodiment can be suitably used as a die attachment material. In such a die attachment material, the silver particles can be sintered together even with low-temperature or short-time heat treatment in the bonding process, regardless of whether pressure is applied or not, to achieve excellent die shear strength. However, when this die attachment material is sintered without pressure, it is preferable to contain more (a) silver fine particles than a pressure sintered die attachment material from the viewpoint of improving sinterability. That is, the content of (a) silver fine particles in (A) silver particles in the pressureless sintered die attachment material is preferably 30 to 65 mass%, more preferably 35 to 60 mass%, even more preferably 40 to 60 mass%, and particularly preferably 45 to 55 mass% in terms of silver relative to 100 mass% of (A) silver particles from the viewpoint of improving sinterability. On the other hand, the content of (a) silver microparticles in (A) silver particles in the pressure sintering type die attach material is preferably 0 to 50 mass%, more preferably 0 to 30 mass%, even more preferably 0 to 15 mass%, and particularly preferably 0 to 10 mass%, calculated as silver, relative to 100 mass% of the (A) silver particles, from the standpoint of cost and from the standpoint of ensuring sinterability and suppressing sintering shrinkage.
[0048] [(B) Solvent] The (B) solvent used in the conductive composition of this embodiment may be any solvent known in the art. For example, alcohol-based solvents such as ethylene glycol, propylene glycol, benzyl alcohol, 2-ethyl-1,3-hexanediol, and dihydroterpineol; aromatic hydrocarbon-based solvents such as toluene, xylene, ethylbenzene, diethylbenzene, isopropylbenzene, amylbenzene, p-cymene, tetralin, and petroleum-based aromatic hydrocarbon mixtures; terpene alcohols such as terpineol, linalool, geraniol, and citronellol; ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono-n-butyl ether, ethylene glycol monophenyl ether, propylene glycol mono-tert-butyl ether, diethylene glycol monoethyl ... Examples of the solvent include ether alcohol solvents such as ethylene glycol monobutyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, and tripropylene glycol monomethyl ether; ketone solvents such as methyl isobutyl ketone; and ester solvents such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, dipropylene glycol monoethyl ether acetate, and 2,2,4-trimethyl-1,3-pentanediol 2-methylpropanoate, water, etc. The solvents may be used alone or in combination of two or more.
[0049] The solvent (B) is preferably, for example, an alcohol-based solvent having a hydroxyl group and a boiling point of 180 to 265°C, preferably 180 to 250°C. Among these, diethylene glycol monobutyl ether acetate, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol 2-methylpropanoate, dihydroterpineol, and benzyl alcohol are preferred, and among these, diethylene glycol monobutyl ether acetate, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol 2-methylpropanoate (common name: Texanol), and diethylene glycol mono-2-ethylhexyl ether are more preferred.
[0050] The content of the (B) solvent in the conductive composition is not particularly limited, but is preferably 1 to 20 mass%, more preferably 1.5 to 18 mass%, and even more preferably 2 to 15 mass%, relative to 100 mass% of the conductive composition. When the content of the (B) solvent in the conductive composition is within the above range, the conductive composition is excellent in stability, the conductive composition can be uniformly applied to the object to be adhered, and the printability and transferability are excellent. In addition, even if the solvent volatilizes during sintering of the (A) silver particles, voids generated at the joint with the object to be adhered are suppressed, and a joint with a desired thickness can be formed.
[0051] [(C) Thermosetting resin] The (C) thermosetting resin used in the conductive composition of this embodiment is a thermosetting resin having an easily saponifiable chlorine concentration of 3,000 to 12,000 ppm. The conductive composition of this embodiment contains 0.1 to 1.5 parts by mass of the (C) thermosetting resin per 100 parts by mass of the (A) silver particles. By containing the above-mentioned predetermined amount of the (C) thermosetting resin having an easily saponifiable chlorine concentration of 3,000 to 12,000 ppm, sufficient die shear strength can be maintained even at low temperature or for a short time sintering. Note that, as described later, easily saponifiable chlorine is generated as an impurity in the manufacturing process of epoxy resins, and is not usually generated in the manufacturing process of thermosetting resins such as (meth)acrylates, bismaleimides, phenolic resins, and silicone resins. However, easily saponifiable chlorine may be added separately to thermosetting resins other than epoxy resins in order to achieve both low temperature or short time sintering and die shear strength. The conductive composition of the present invention can be used mainly as a sintered die attach material, and the curing agent and curing accelerator are not essential components. However, it is also possible to add a curing agent as an optional component, for example, for the purpose of reducing the elastic modulus of the conductive composition.
[0052] The content of the (C) thermosetting resin in the conductive composition is 0.1 to 1.5 parts by mass per 100 parts by mass of the (A) silver particles, as described above, but the content may be adjusted appropriately depending on the easily saponifiable chlorine concentration of the (C) thermosetting resin. That is, the (C) thermosetting resin may have an easily saponifiable chlorine concentration in the range of 3,000 to 12,000 ppm. For example, when a relatively high concentration of the (C) thermosetting resin is used within the above concentration range, an effective effect on sinterability can be obtained even if the content of the (C) thermosetting resin is relatively small. On the other hand, when a relatively low concentration of the (C) thermosetting resin is used within the above concentration range, the effect on sinterability can be improved by slightly increasing the content of the thermosetting resin compared to when a high concentration is used.
[0053] The types of the (C) thermosetting resin include epoxy resins, (meth)acrylates, bismaleimides, phenolic resins, silicone resins, etc. However, the (C) thermosetting resin used in the conductive composition of the present embodiment is a thermosetting resin containing easily saponifiable chlorine, and as described above, it is necessary that the easily saponifiable chlorine concentration is in the range of 3,000 to 12,000 ppm.
[0054] "Easily saponifiable chlorine" refers to chlorine species that exist as 1,2-chlorohydrin, which is generated when dehydrochlorination is incomplete. Examples of easily saponifiable chlorine include 1,2-chlorohydrin, 1,3-chlorohydrin, and 1-chloromethyl-2-glycidyl ether (chloromethyl) forms. These are usually generated as impurities during the manufacturing process of epoxy resins.
[0055] Examples of the 1,2-chlorohydrin compound include a compound represented by the general formula (1). Examples of the 1,3-chlorohydrin compound include a compound represented by the general formula (2). Examples of the chloromethyl compound include a compound represented by the general formula (3). In the following general formulas (1) to (3), R 1 , R 2 , R 3 and R 4 are each independently a hydrogen atom or a methyl group, and n is an integer of 0 to 30, preferably 0 to 20, and more preferably 0 to 10.
[0056] [ka]
[0057] [ka]
[0058] [ka]
[0059] (C) The thermosetting resin preferably contains an epoxy resin. There is no particular limitation on the type of epoxy resin, and known epoxy resins can be used. For example, bisphenol A type, bisphenol F type, biphenyl type, tetramethylbiphenyl type, cresol novolac type, phenol novolac type, bisphenol A novolac type, dicyclopentadiene phenol condensation type, phenol aralkyl condensation type, glycidylamine type, and other epoxy resins, brominated epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins can be mentioned. These epoxy resins can be used alone or in combination of two or more types.
[0060] (C) Examples of epoxy resins used as thermosetting resins include "EPOX-MK R540 (trade name)" manufactured by Printec Co., Ltd., "AK-601 (trade name)" manufactured by Nippon Kayaku Co., Ltd., and "EX-722L (trade name)" and "EX-521 (trade name)" manufactured by Nagase ChemteX Corporation. The easily saponifiable chlorine concentration of "EPOX-MK R540" is about 8000 to 9000 ppm. The easily saponifiable chlorine concentration of "AK-601" is about 6000 ppm. The easily saponifiable chlorine concentration of "EX-722L" is about 4000 ppm. The easily saponifiable chlorine concentration of "EX-521" is about 5000 to 6000 ppm. The easily saponifiable chlorine concentrations mentioned above are actual measured values, and the measurement method will be described later. These epoxy resins can be used alone or in combination of two or more types.
[0061] The easily saponifiable chlorine concentration of the (C) thermosetting resin is 3,000 to 12,000 ppm, preferably 5,000 to 12,000 ppm, more preferably 6,000 to 12,000 ppm, and even more preferably 7,000 to 12,000 ppm.
[0062] In the conductive composition of this embodiment, the mass ratio of the (C) thermosetting resin to 100 parts by mass of the (A) silver particles is 0.1 to 1.5 parts by mass. The mass ratio of the (C) thermosetting resin to 100 parts by mass of the (A) silver particles is preferably 0.1 to 1.3 parts by mass, more preferably 0.1 to 0.7 parts by mass, and even more preferably 0.1 to 0.4. If the mass ratio of the (C) thermosetting resin to 100 parts by mass of the (A) silver particles exceeds 1.5 parts by mass, the amount of the (C) thermosetting resin relative to the (A) silver particles becomes large, and sintering inhibition may easily occur. On the other hand, if the mass ratio of the (C) thermosetting resin to 100 parts by mass of the (A) silver particles is less than 0.1 parts by mass, it becomes difficult to maintain sufficient die shear strength in sintering at a low temperature or for a short time.
[0063] The following method can be used to measure the easily saponifiable chlorine concentration of (C) thermosetting resin. First, 25 mL of 2-butanone is added to 1 g of the (C) thermosetting resin to be measured and dissolved. Next, 25 mL of 2-butoxyethanol is further added to the obtained solution. Next, 25 mL of 1 mol / L sodium hydroxide solution is added to the obtained solution and mixed. Next, the obtained solution is left at room temperature of 25°C for 60 minutes. Next, 25 mL of acetic acid is further added to the solution that has been left for 60 minutes and mixed to obtain a sample solution. Then, a silver electrode is immersed in the obtained sample solution and potentiometric titration is performed with a 0.01 mol / L silver nitrate solution to determine the easily saponifiable chlorine concentration.
[0064] The conductive composition of the present embodiment can be printed or applied to a desired portion of a substrate or the like by a conventionally known method such as screen printing, and then a semiconductor element or the like is placed on the composition as a component. The composition is then heated to a predetermined temperature and sintered to form a joint, thereby forming an electronic component.
[0065] The conductive composition of the present embodiment can be used to form conductive circuits on printed circuit boards, electrodes of capacitors, and the like, but by taking advantage of the properties described above, it can also be suitably used for joining components of electronic components such as semiconductor devices, or joining substrates and components, etc.
[0066] [Method of manufacturing conductive composition] The method for producing the conductive composition of the present embodiment is not particularly limited, and the conductive composition can be produced by adding each component in a predetermined ratio to a mixer such as a planetary mixer, a dissolver, a bead mill, a Raikai mixer, a pot mill, a triple roll mill, a rotary mixer, or a twin-shaft mixer, and mixing them.
[0067] [Die attach material] Next, an embodiment of the die attachment material of the present invention will be described. The embodiment of the die attachment material of the present invention is a die attachment material containing the conductive composition described above. The conductive composition contains (A) silver particles having an average particle size of 0.05 to 5 μm, (B) a solvent, and (C) a thermosetting resin, in which the easily saponifiable chlorine concentration of the (C) thermosetting resin is 3,000 to 12,000 ppm, and the (C) thermosetting resin is contained in an amount of 0.1 to 1.5 parts by mass per 100 parts by mass of the (A) silver particles.
[0068] The die attachment material of the present embodiment is particularly suitable for application as a die attachment material for the joint of a semiconductor device as an electronic component. Conventionally, lead solder has been widely used as a die attachment material, but due to the harmfulness of lead, restrictions on the use of lead in various countries are becoming stricter. The die attachment material containing the conductive composition of the present invention exhibits a thermal conductivity equal to or higher than that of lead (generally 35 to 65 W / mK) and also has good electrical conductivity, so it can be a highly thermally conductive die attachment material that can replace lead solder. The die attachment material of the present embodiment is suitable as a die attachment material for forming a joint for joining, for example, a silicon die as a semiconductor device. In addition to silicon dies, various materials such as SiC and GaN can be used.
[0069] The die attachment material of this embodiment can realize excellent die shear strength by sintering silver particles together even at low temperatures or for a short time during the bonding process, regardless of whether pressure is applied or not. That is, the die attachment material of this embodiment may be a pressureless sintered die attachment material in which silver particles are sintered together by heating alone, without pressure, during the bonding process to form a bond, or a pressure sintered die attachment material in which silver particles are sintered together by heating while applying pressure to form a bond. The die attachment material can be fired in an inert gas such as a nitrogen atmosphere or in the air. Examples of firing equipment include known electric furnaces, air blowers, belt furnaces, and the like.
[0070] There are no particular limitations on the pressureless bonding conditions in the bonding process using the die attach material, but for example, the heating temperature for the pressureless sintered die attach material is preferably 175 to 280° C., more preferably 175 to 250° C., and even more preferably 200 to 250° C. The heating time can be appropriately changed depending on the heating temperature, but can be, for example, 20 to 120 minutes, and preferably 20 to 60 minutes.
[0071] On the other hand, in the bonding process using the die attachment material, there are no particular limitations on the bonding conditions involving pressurization, but for example, the heating temperature for the pressure sintered die attachment material can be preferably 250 to 310° C., more preferably 265 to 310° C., and even more preferably 280 to 300° C. The heating time can be appropriately changed depending on the heating temperature, but can be, for example, 2 to 10 minutes, and preferably 2 to 5 minutes. The pressure can be, for example, 5 to 20 MPa, and preferably 8 to 15 MPa.
[0072] Pressure sintered die attachment materials are pre-dried (for example, pre-dried at 120°C for 15 minutes) before the main sintering. By containing a thermosetting resin (C) like the die attachment material of this embodiment, the thermosetting resin does not volatilize during pre-drying and remains, and the thermosetting resin exerts the effects of the present invention during the main sintering, making the die attachment material easy to handle.
[0073] [Electronic components] Next, an embodiment of the electronic component of the present invention will be described. The embodiment of the electronic component of the present invention is an electronic component having a sintered body of the conductive composition described above. The conductive composition contains (A) silver particles having an average particle size of 0.05 to 5 μm, (B) a solvent, and (C) a thermosetting resin, and the easily saponifiable chlorine concentration of the (C) thermosetting resin is 3,000 to 12,000 ppm, and contains 0.1 to 1.5 parts by mass of the (C) thermosetting resin per 100 parts by mass of the (A) silver particles. In the electronic component of this embodiment, the sintered body of the conductive composition forms a joint that joins components of an electronic component such as a semiconductor device to each other, or joins a substrate to a component, etc. EXAMPLES
[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0075] The analyses in the examples were carried out as follows.
[0076] [Average particle size of silver particles and silver microparticles] The average particle size of silver particles and silver microparticles is the average particle diameter (number average) when 200 random particles are observed with a scanning electron microscope (SEM). The scanning electron microscope (SEM) used was S-3400N (Hitachi High-Technologies Corporation).
[0077] (1) Concentration of easily saponifiable chlorine in thermosetting resins 25 mL of 2-butanone was added to 1 g of the thermosetting resin to be measured and dissolved. Next, 25 mL of 2-butoxyethanol was further added to the obtained solution. Next, 25 mL of 1 mol / L NaOH solution was added to the obtained solution and mixed. Next, the obtained solution was left at room temperature of 25°C for 60 minutes, and 25 mL of acetic acid was further added to the solution after leaving it and mixed to obtain a sample solution. A silver electrode was immersed in the obtained sample solution and potentiometric titration was performed with 0.01 mol / L silver nitrate solution to measure the easily saponifiable chlorine concentration (ppm).
[0078] (2) Measurements of conductive compositions (2-1) Preparation of test specimens and pressure bonding conditions The conductive composition was applied to a 1 mm thick silver-plated copper substrate so as to have a width of 10 mm, a length of 10 mm, and a thickness of 150 μm, and then dried at 120° C. for 15 minutes in an air atmosphere. Then, a 3 mm silver-plated copper chip was placed on the dried coating. Next, the temperature of the head and stage of the pressure device was set to 280° C. Then, the test piece was placed on the stage of the pressure device, and pressure was immediately started. The pressure was applied from 0 MPa to 8 MPa at a constant speed for 10 seconds, and then the pressure of 8 MPa was maintained for 3 minutes. After 3 minutes, the pressure bonding was terminated, and the test piece was quickly removed. All of the pressure bonding was performed in an air atmosphere. In addition, for the test pieces of each example and comparative example, those that were subjected to pressure bonding are indicated as "pressurized" in the "pressurized / non-pressurized" column of Tables 1 to 3. (2-2) Preparation of test specimens and pressureless joining conditions The conductive composition was applied to a 1 mm thick silver-plated copper substrate so as to have a width of 10 mm, a length of 10 mm, and a thickness of 150 μm, and then a 3 mm silver-plated copper chip was placed on the coating. The test piece was then placed in an oven set at 100° C. and left for 30 minutes. After leaving for 30 minutes, the test piece was removed from the oven and quickly placed in another oven set at 250° C. After leaving for 20 minutes, the test piece was removed. All of the above pressureless bonding was performed in an air atmosphere. Note that, for the test pieces of each Example and Comparative Example that were subjected to pressureless bonding, "pressureless" is indicated in the "pressure / no pressure" column of Tables 1 to 3. (2-3) Die shear strength (bonding strength) The die shear strength of the test pieces bonded under the above-mentioned pressure bonding conditions or non-pressure bonding conditions was measured using a bond tester manufactured by Nordson Advanced Technology (Universal Bond Tester Series 4000 (product name)). (2-4) Evaluation method (judgment) The test pieces of each of the examples and comparative examples were evaluated according to the following evaluation criteria. Evaluation "Excellent": Die shear strength is 65 MPa or more. Evaluation "Good": The die shear strength is 50 MPa or more and less than 65 MPa. Evaluation: "Fail": The die shear strength is less than 50 MPa. In Tables 1 to 3, an "excellent" evaluation is indicated by "◎", a "good" evaluation is indicated by "◯", and a "poor" evaluation is indicated by "×".
[0079] The components used in the examples are as follows.
[0080] <(A) Silver particles> (A-1) Spherical silver particles with an average particle size of 0.9 μm The silver particles (A-1) were produced according to the method for producing silver particles described in Example 1 of JP 2016-33259 A. Observation with a scanning electron microscope (SEM) confirmed that the average particle size of the silver particles was 0.9 μm. (A-2) Spherical silver particles with an average particle size of 1.2 μm (K-0082P (product name), manufactured by Metallo Technology Co., Ltd.) (A-3) Spherical silver particles with an average particle size of 0.15 μm The silver fine particles (A-3) were produced according to the method for producing silver fine particles described in Example 1 of JP-A No. 2006-183072. As a result of observation with a scanning electron microscope (SEM), it was confirmed that the average particle size of the silver fine particles was 0.15 μm. (A-4) Spherical silver particles with an average particle size of 0.4 μm The silver particles (A-4) were prepared according to the method for producing silver particles described in paragraph
[0083] of International Publication No. 2017 / 204238. As a result of observation with a scanning electron microscope (SEM), it was confirmed that the average particle size of the silver particles was 0.4 μm.
[0081] <(B) Solvent> (B-1) 2-Ethyl-1,3-hexanediol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B-2) Texanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0082] <(C) Thermosetting resin> (C-1) Epoxy resin (manufactured by Nagase Chemtex Corporation, EX-722L (trade name), easily saponifiable chlorine concentration: 4000 ppm) (C-2) Epoxy resin (manufactured by Nagase Chemtex Corporation, EX-521 (trade name), easily saponifiable chlorine concentration: 6000 ppm) (C-3) Epoxy resin (EPOX-MK R540 (trade name), manufactured by Printec Co., Ltd., easily saponifiable chlorine concentration: 8000 ppm) (C-4) Epoxy resin (by-product of the distillation of AK-601 (trade name), manufactured by Nippon Kayaku Co., Ltd., easily saponifiable chlorine concentration: 11,000 ppm) (C-5) Epoxy resin (manufactured by Nagase Chemtex Corporation, EX-722P (trade name), easily saponifiable chlorine concentration: 60 ppm) (C-6) Epoxy resin (manufactured by Nippon Kayaku Co., Ltd., distilled product of AK-601 (trade name), easily saponifiable chlorine concentration: 1000 ppm) (C-7) Acrylate (Kyoeisha Chemical Co., Ltd., Light Acrylate DCP-A (product name)) The (C-4) epoxy resin is an epoxy resin containing a high concentration of easily saponifiable chlorine components generated as a by-product when AK-601 (trade name) is distilled.
[0083] The conductive compositions of the Examples and Comparative Examples were prepared using the components shown in Tables 1 to 3 in the ratios shown in Tables 1 to 3. Specifically, the components shown in Tables 1 to 3 were stirred and degassed using a rotary / revolution mixer to make them uniform, thereby preparing the conductive compositions of the Examples and Comparative Examples. The die shear strength of the obtained conductive compositions was measured by the above-mentioned test method, and a judgment was made based on the above-mentioned evaluation method. The ratios shown in Tables 1 to 3 are in parts by mass. The results are shown in Tables 1 to 3.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] As shown in Tables 1 and 2, the joints formed using the conductive compositions of Examples 1 to 16 had excellent die shear strength (bonding strength) of 50 MPa or more. The conductive compositions of Examples 1 to 16 also had excellent die shear strength, whether the joints were formed by pressure bonding as in Examples 1 to 14 and 16, or by non-pressure bonding as in Example 15. In particular, the joints formed using the conductive composition of Example 4 had excellent die shear strength, and it was confirmed that when the easily saponifiable chlorine concentration of the thermosetting resin (C) was decreased or increased for this conductive composition, the die shear strength (bonding strength) tended to gradually decrease.
[0088] In addition, when comparing the die shear strength of the joint formed using the conductive composition of Examples 1 and 2, the joint formed using the conductive composition of Example 2 containing (A-3) silver microparticles exhibited a higher value. This shows that the inclusion of silver microparticles having a number-average particle size on the order of submicrons improves the die shear strength of the joint.
[0089] It was also found that even when two types of epoxy resins were used in combination as in the conductive composition of Example 16, the die shear strength of the joint was improved by adjusting the easily saponifiable chlorine concentration to satisfy a desired numerical range. The conductive composition of Example 13 was a combination of (C-3) epoxy resin with an easily saponifiable chlorine concentration of 8000 ppm and (C-7) acrylate that was substantially free of easily saponifiable chlorine as the thermosetting resin (C), and it was found that the die shear strength of the joint was also improved for such a conductive composition.
[0090] On the other hand, the conductive compositions of Comparative Examples 1 to 4, 7, and 8 had a low easily saponifiable chlorine concentration in the (C) thermosetting resin, or contained substantially no easily saponifiable chlorine, and had low die shear strength at the joint. The conductive composition of Comparative Example 5 had a low blend amount of the (C-3) epoxy resin as the (C) thermosetting resin, and had low die shear strength at the joint. Moreover, the conductive compositions of Comparative Examples 6 and 9 had a high blend amount of the (C-3) epoxy resin as the (C) thermosetting resin, and had low die shear strength at the joint. [Industrial Applicability]
[0091] The conductive composition of the present invention can be used for bonding each member of a semiconductor device and an electric / electronic component, such as a die attachment material. The die attachment material and pressure sintered die attachment material of the present invention are die attachment materials containing the conductive composition of the present invention, and can be used for bonding each member of a semiconductor device and an electric / electronic component. The electronic component of the present invention can be used in the fields of semiconductor devices and electric / electronics.
Claims
1. (A) silver particles having an average particle size of 0.05 to 5 μm, (B) a solvent, and (C) a thermosetting resin; (C) the thermosetting resin includes an epoxy resin; (C) the easily saponifiable chlorine concentration of the thermosetting resin is 3,000 to 12,000 ppm; A conductive composition comprising 0.1 to 1.5 parts by mass of a thermosetting resin (C) per 100 parts by mass of silver particles (A).
2. The conductive composition according to claim 1, wherein the silver particles (A) comprise fine silver particles having an average particle size of 0.05 to 0.5 μm.
3. A die attach material comprising the conductive composition according to claim 1 or 2.
4. A pressure sintered die attach material comprising the conductive composition according to claim 1 or 2.
5. An electronic component comprising a sintered body of the conductive composition according to claim 1 or 2.
Citation Information
Patent Citations
Electroconductive resin paste
JP1985001221A
Epoxy resin composition for semiconductor sealing
JP1988017925A
Conductive material
JP2015004016A
Thermosetting resin composition, semiconductor device and electric and electronic parts
JP2016023256A
Conductive composition, solar cell, and solar cell module
JP2016160413A